Neuroticism, emotional stress reactivity and recovery in daily life: Examining extraversion and openness as moderators - Lücke, Anna J.; Schilling, Oliver; Kunzmann, Ute; Gerstorf, Denis; Katzorreck-Gierden, Martin; Hoppmann, Christiane A.; Luong, Gloria; Wagner, Gert G.; Riediger, Michaela; Wrzus, Cornelia (Journal of research in personality, 2024)
Emotional stressor reactivity and recovery from stressors are associated with the personality trait neuroticism. We examined whether higher extraversion or openness might buffer these associations in daily life. Participants from two age-heterogeneous samples (lifespan: n = 364, aged 14-88 years; late adulthood: n = 170, aged 66-89 years) answered personality questionnaires and reported their momentary negative affect (NA) and stressors six times per day over nine or seven days, respectively. Higher neuroticism was associated with higher overall NA in both samples, but with more pronounced stressor reactivity only in the late adulthood sample. Neither extraversion nor openness moderated associations between neuroticism and stressor reactivity or recovery. We discuss the role of different personality traits in stress processes for different age groups.
Online veröffentlicht: 28. Februar 2024
Gesehen am 19.08.2024